Usability issues in mobile learning: Students' perceptions in Pakistani universities - Imtinan, Umera; Chang, Vanessa; Issa, Tomayess (QScience, 2013)
Usability in mobile devices, for learning, has drawn researchers’ attention since the term mobile learning has been coined in teaching and learning arenas. Current mobile devices in the market have ignored the design and styles for learning purposes. Although mobile devices have some features for games purposes, there are other important usability characteristics that ought to be considered to support learning. Therefore, mobile learning researchers need to investigate the learning options with the available capabilities of mobile devices. Students in developing countries reported more problems related to usability based on their individual experiences dealing with mobile devices for learning purposes. This paper aims to identify the implications of usability in mobile devices for learning based on research conducted in Pakistan.